VD_FINDINFO AP / 2011 / 118 vom 21. Juli 2010 - VD Tribunal cantonal (2010)
AMENDE, CONVERSION DE L'AMENDE, FIXATION DE L'AMENDE, PEINE PÉCUNIAIRE | 106 al. 2 CP, 106 al. 3 CP, 106 CP, 34 al. 1 CP, 415 CPP